Choroidal abnormalities in neurofibromatosis type 1 detected by near‐infrared reflectance imaging in paediatric population. (19th May 2015) - Vagge, Aldo; Camicione, Paola; Capris, Cristina; Sburlati, Carlo; Panarello, Simona; Calevo, Maria Grazia; Traverso, Carlo Enrico; Capris, Paolo
Abstract: Purpose: To investigate choroidal abnormalities in paediatric patients with neurofibromatosis type 1 (NF1) detected by near‐infrared reflectance (NIR) retinography in order to evaluate diagnostic accuracy. Methods: Seventy‐eight paediatric patients with NF1, diagnosed according to the National Institutes of Health (NIH) criteria, and 96 healthy control subjects matched for age were examined. Enrolled patients were under 16 years old. The presence of choroidal abnormalities was investigated by confocal scanning laser ophthalmoscopy. Main outcome measure was to evaluate diagnostic accuracy in paediatric patients compared with the NIH criteria. Results: Seventy‐eight patients with NF1 (41 female, 37 male; mean age 8.1 ± 3.5 years) were compared with 96 healthy control subjects (42 female, 54 male; mean age 8 ± 3 years). Choroidal abnormalities were observed in 54 (69.2%) of the patients with NF1. As regards the fundus topographical distribution, choroidal abnormalities were more frequent at the posterior pole with a statistically significant correlation between patient age and the number of involved choroidal areas (Spearman r  = 0.23; p < 0.04). No choroidal abnormalities were present in the control group. Detection accuracy of choroidal nodules was 70%. Conclusion: Choroidal abnormalities appearing as bright patchy regions detected by NIR imaging occurred very frequently in paediatric patients affected by NF1. The present study appears to show that NIR used to detect choroidal involvement allows for elevated diagnostic accuracy.